Antibodies to myelin oligodendrocyte glycoprotein in aquaporin 4 antibody seronegative longitudinally extensive transverse myelitis: Clinical and prognostic implications. (March 2016) - Cobo-Calvo, Álvaro; Sepúlveda, María; Bernard-Valnet, Raphael; Ruiz, Anne; Brassat, David; Martínez-Yélamos, Sergio; Saiz, Albert; Marignier, Romain
Objective: We aimed to investigate the frequency and clinical significance of antibodies to myelin oligodendrocyte glycoprotein (MOG-abs) in patients who presented with a first episode of seronegative aquaporin 4 antibody (AQP4-ab) longitudinally extensive transverse myelitis (LETM). Methods: Epidemiological, clinical, and paraclinical data of 56 patients from three European centres were analysed. Patients were retrospectively tested for MOG-abs and AQP4-abs, by cell-based assays. Findings: Thirteen (23.2%) patients were MOG-ab positive. Among the 56 patients, six (10.7%) converted to neuromyelitis optica (NMO), one (1.8%) to multiple sclerosis (MS), nine (16.1%) had recurrent LETM, and 40 (71.4%) remained as monophasic LETM. Compared with seronegative patients, those with MOG-abs were younger (median: 32.5 vs 44 years; p =0.007), had cerebrospinal fluid pleocytosis more frequently (94% vs 45%, p =0.003) and had better outcome (median Expanded Disability Status Scale (EDSS) 2.0 vs 3.0, p =0.027). MOG-ab positive patients also showed an increase risk of optic neuritis relapse and NMO conversion ( p =0.010). Conclusion: Patients with MOG-abs in AQP4-ab seronegative LETM have clinical distinctive features, higher risk of optic neuritis relapses, and better outcome than patients seronegative.